PRIMARY CENTRAL NERVOUS SYSTEM LYMPHOMAS - Adriana Octaviana Dulamea (Romanian Journal of Neurology, 2015)
Primary central nervous system lymphoma (PCNSL) is an aggressive non-Hodgkin B-cell lymphoma with characteristic clinical behavior, biological features and poor prognosis despite complex treatment. PCNSL has a median survival of 17 to 45 months in immunocompetent patients, and only 20-30% of cases can be cured successfully. Clinical outcome has improved since the advances in combination chemotherapy protocols, addition of whole brain radiation therapy, encouraging responses of rituximab adminsitration in refractory PCNSL and autologous hematopoietic stem-cell transplantation as consolidative therapy. The author review the recent data on pathogenesis, diagnostic methods and treatment strategies of PCNSL in immunocompetent patients.